An antibody-drug conjugate targeting soluble and membrane-bound TGFα is effective against pancreatic tumors - Inés Romero-Pérez; Juan Carlos Montero; Mónica Redondo-Puente; María del Carmen Gómez-García; Mireia Morell-Ginestà; Gabriel Capellá; Atanasio Pandiella (Journal of Experimental & Clinical Cancer Research)
Abstract Background Pancreatic cancer is one of the most difficult to treat neoplasias. Because of that, the prognosis of the disease is dismal, and identification of novel therapeutic approaches is needed. This study investigates the role of transforming growth factor-alpha (TGFα) in pancreatic cancer and its potential as a therapeutic target. Methods Using in silico platforms, it was confirmed that TGFA, the gene encoding TGFα, is significantly overexpressed in pancreatic adenocarcinomas relative to normal pancreatic tissues. In patient-derived xenografts as well as in pancreatic cancer cell lines, multiple molecular forms of TGFα were identified, including the transmembrane TGFα precursor (proTGFα) and the soluble 6 kDa mature form. Functional assays using RNA interference and CRISPR/Cas9 demonstrated that TGFA knockdown significantly impaired cell proliferation, reinforcing the critical role of TGFα in driving tumor growth. The therapeutic potential of targeting TGFα was evaluated through the development of two monoclonal antibodies (5F1 and 16B10) specific for TGFα. Results These antibodies effectively bound to proTGFα-expressing cells, with minimal off-target effects in TGFA-knockout cell lines. When conjugated to cytotoxic agents such as MMAF, the resulting antibody-drug conjugates (ADCs) exhibited potent antiproliferative activity, significantly reducing the viability of TGFα-expressing pancreatic cancer cells. Mechanistic studies revealed that MMAF-loaded ADCs induced G2/M cell cycle arrest, with markers of mitotic disruption evident in treated cells. In vivo, the TGFα-targeting ADCs elicited substantial tumor regression in murine models of pancreatic cancer, whereas the unconjugated antibodies merely stabilized tumor growth. Conclusions These findings highlight TGFα as a promising therapeutic target in pancreatic cancer, supporting further preclinical and clinical development of TGFα-directed ADCs.